If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5h(-2k + 4) = 0 Reorder the terms: 5h(4 + -2k) = 0 (4 * 5h + -2k * 5h) = 0 (20h + -10hk) = 0 Solving 20h + -10hk = 0 Solving for variable 'h'. Move all terms containing h to the left, all other terms to the right. Factor out the Greatest Common Factor (GCF), '10h'. 10h(2 + -1k) = 0 Ignore the factor 10.Subproblem 1
Set the factor 'h' equal to zero and attempt to solve: Simplifying h = 0 Solving h = 0 Move all terms containing h to the left, all other terms to the right. Simplifying h = 0Subproblem 2
Set the factor '(2 + -1k)' equal to zero and attempt to solve: Simplifying 2 + -1k = 0 Solving 2 + -1k = 0 Move all terms containing h to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + -1k = 0 + -2 Combine like terms: 2 + -2 = 0 0 + -1k = 0 + -2 -1k = 0 + -2 Combine like terms: 0 + -2 = -2 -1k = -2 Add 'k' to each side of the equation. -1k + k = -2 + k Combine like terms: -1k + k = 0 0 = -2 + k Simplifying 0 = -2 + k The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined.Solution
h = {0}
| 4z-(z+6)=6y-3(y-3) | | 4y+2(6y+12)= | | 5(n^2-8n+15)=0 | | 3x-7=5x | | (x+15)=-16 | | -12.5h+14.2-1.4-2.7h= | | 220-5x=31x+20 | | -(5y+2)-(-4y-7)=1 | | -3t+2=1 | | 9x+6=7x | | y=0.85x-4 | | -3+2=1 | | 9g-15-12g+17= | | 8x-3=7x-10 | | 6x-33=14x-29 | | 4(n+3)-2n=3(n-3) | | x^2-14x-95=0 | | (15x-2x)-(20x-2x)=234 | | -2(17)-(2x)=-486 | | 15-x=4x-9 | | x+3(2x+5)=-20 | | -9k-12=8-4k | | h=-16t^2+32t | | -9k-12=4k-8 | | 7+2x-5=9x+6-5x | | g(3)=-3(3)+5 | | (3m+13)+(4m+6)= | | 3x+5(3x-5)=25 | | 16t= | | 2(x-4)+10=18 | | 5xy-2x=19 | | 5(7+3k)=9(k-4) |